Exploring principals' institutional instructional leadership practices in primary schools: a case study of two underperforming township primary schools in Ekurhuleni South District, Gauteng province - Vilakazi, Nicholas Sibusiso (My University, 2016)
Instructional Leadership has been researched extensively in secondary schools in South Africa, and not much is known about it in South African primary schools. Instructional Leadership is concerned with teaching and learning and the behaviour of teachers in enhancing student or learner performance as the core business and function of schools. However, many principals in the low-functioning township primary schools do not conceptualise instructional leadership as such. Many of these schools continue to perform poorly academically. In a longitudinal study for the Matthew Goniwe School of Leadership and Governance (MGSLG) it was discovered that more than 500 school principals in Gauteng province did not conceptualise instructional leadership as their main role. The management of teaching and learning was ranked only seventh out of ten leadership activities. Principals shift their instructional leadership role to deputy principals and Head of Departments. This research explores principals’ structional leadership practices in relation to student achievement. This study employs a mixed-method approach which incorporates a qualitative and quantitative design and observation of principals’ instructional leadership practices. The participants in the study involve all levels of the teaching force which includes the principal, the deputy principal, the Head of Department (HoD) and the teachers in two township primary schools. The research findings reveal that school principals shift their instructional leadership to their lower level management colleagues. Key words: Instructional leadership, distributed leadership, student achievement, under-performance, curriculum management
A thesis submitted to the Wits School of Education, Faculty of Humanities, University of the Witwatersrand in fulfilment of the requirements for the Degree of Master of Education. Johannesburg 2016
Keywords: Elementary school principals--South Africa--Ekurhuleni; Education, Elementary--South Africa; School management and organization--South Africa--Ekurhuleni; Educational leadership--South Africa